2017
DOI: 10.1071/sr15322
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic and organomineral fractions as indicators of the effects of land management in conventional and organic sugar cane systems

Abstract: Brazilian sugar cane production has undergone changes in residue management. To better understand the dynamics of soil C and N in soil organic matter (SOM) fractions resulting from sugar cane management practices, we determined: the effects of different sugar cane management on the C and N content of SOM fractions; the effects of crop management, soil texture, depth and different organic matter additions on changes in 13C/12C and 15N/14N isotope composition; and the amount of SOC derived from different sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…To evaluate the influence of microbial indicators on the dynamics of C and N, soil OM was physically fractionated from a soil air-dried mass (20 g) using the granulometric method (Brandani et al, 2017 ). This process, separates organic (OF) (2,000–75 μm), organic-mineral 1 (OMinF1) (2,000–75 μm), organic-mineral 2 (OMinF2) (75–53 μm) and organic-mineral 3 (OMinF3) (<53 μm) fractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the influence of microbial indicators on the dynamics of C and N, soil OM was physically fractionated from a soil air-dried mass (20 g) using the granulometric method (Brandani et al, 2017 ). This process, separates organic (OF) (2,000–75 μm), organic-mineral 1 (OMinF1) (2,000–75 μm), organic-mineral 2 (OMinF2) (75–53 μm) and organic-mineral 3 (OMinF3) (<53 μm) fractions.…”
Section: Methodsmentioning
confidence: 99%
“…C and N concentrations in each OM fraction were determined by dry combustion with an elemental analyzer (LECO®) (Nelson and Sommers, 1982 ; Christensen, 2001 ; Signor et al, 2014 ). TOC and Total-N contents in soil OM fractions were obtained by multiplying C and N concentrations of each fraction by their corresponding mass (Brandani et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although it represents a small proportion of total soil mass, it contains a significant part of the total soil C and N, so that its evaluation can provide an early indication of changes in land use and soil management [107]. Brandani et al [108] verified that burnt harvest combined with organic management was a strategy for long-term storage of total C and N in the light organic fraction, which were related to the quality (diversity) and quantity (frequency) of organic residue addition [107].…”
Section: Green Harvest Managementmentioning
confidence: 99%
“…Evaluating the C content of different particle-size fractions can therefore improve our understanding of the mechanisms by which the soil C stabilisation occurs, as well as the sensitivity of SOM content in response to management practice (Brandani et al 2016). Recent studies appraising different sugarcane management practices have reported changes in C measured in different soil fractions (Brandani et al 2016;Lisboa et al 2009;Signor et al 2014). Brandani et al (2016) highlighted that the cessation of burning combined with organic fertiliser inputs is able to accumulate soil C in at least three SOM fractions (< 53 μm; 75-53 μm and 2000-75 μm).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies appraising different sugarcane management practices have reported changes in C measured in different soil fractions (Brandani et al 2016;Lisboa et al 2009;Signor et al 2014). Brandani et al (2016) highlighted that the cessation of burning combined with organic fertiliser inputs is able to accumulate soil C in at least three SOM fractions (< 53 μm; 75-53 μm and 2000-75 μm). Additionally, Signor et al (2014) showed that cessation of burning can also lead to increased soil C stocks particularly in organo-mineral complexes that typically have a higher mean residence time in the soil than particulate organic matter.…”
Section: Introductionmentioning
confidence: 99%